La maquette, un outil au service d’une éducation aux risques - David Bédouret; Raphaël Chalmeau; Christine Vergnolle-Mainar; Marie Pierre Julien; Jean-Yves Léna; Anne Calvet (M@ppemonde)
Scale models efficiently teach about risks. They can promote a culture of risk management, raise awareness of the vulnerability of nearby and lived-in territories, and encourage debate around societal resilience. The educational framework established around the building of a scale model brings together students and local stakeholders, increasing dialogue and debate. Thus, within this framework, scale models are a heuristic and prospective tool for citizenship education.